Advocating for a participatory approach to One Health capacitation in Malawi - Wood, C.; Parker, L.; Richards, Shauna; Mutua, Florence K.; Wawire, P.; Munthali, B.; Mtegha, C. (CAB International, 2024)
Malawi, a densely populated, land-locked country with high poverty rates, relies heavily on subsistence agriculture, making it vulnerable to food insecurity, weak infrastructure, climate shocks, and infectious diseases. Environmental degradation worsens these issues. One Health (OH) solutions are vital for improving human, animal, and environmental health. OH collaboration can prevent zoonotic diseases, improve health outcomes, and promote sustainability by sharing resources and adopting a holistic approach, thereby enhancing public health efficiency, reducing costs, and building resilience. A baseline assessment by Malawi’s COHESA project revealed strengths in OH, with strong research institutions like Malawi Liverpool Wellcome Trust (MLW), Lilongwe University of Agriculture and Natural Resources (LUANAR), and Malawi University of Science and Technology (MUST). However, the OH landscape is fragmented, lacking interconnected systems. Challenges include limited formalized research agreements, lab capacity, and infrastructure in rural areas. Governance gaps include low political priority, outdated policies, and insufficient funding, while education faces limited interdisciplinary collaboration and supportive policies. Despite these challenges, stakeholders recognize OH’s value, and initiatives like Technical Working Groups and international collaborations are underway to address gaps and improve training programs.